The Circulation of Care in Multilingual and Transnational Children. (November 2020) - Kwon, Jungmin
Employing a multisited ethnographic stance, this study examined second-generation Korean immigrant children who sustain linkages with their parental homelands to better understand how transnationalism shapes their language and literacy practices by documenting their experiences in and across multiple spaces in North Carolina, the United States, and Seoul, South Korea. Findings suggest that the circulation of care, or the multidirectional and reciprocal exchange of support and care, functioned at the center of the children's multilingual and transnational lives. The children actively engaged in language and literacy interactions through which they forged and extended meaningful ties with their parental homelands and strengthened intergenerational relationships. This study challenges the binary and fixed notions of home/host countries and highlights the need for longitudinal, multisited research on immigrant children's transnational journeys with careful attention to the mobility of their language and literacy across generations and countries.